Pulmonary Deposition of Radionucleotide-Labeled Palivizumab: Proof-of-Concept Study - Rajapaksa, Anushi E.; Do, Lien Anh Ha; Suryawijaya Ong, Darren; Sourial, Magdy; Veysey, Duncan; Beare, Richard; Hughes, William; Yang, William; Bischof, Robert J.; McDonnell, Amarin; Eu, Peter; Yeo, Leslie Y.; et al. (Frontiers in Pharmacology, 2020)
Objective Current prevention and/or treatment options for respiratory syncytial virus (RSV) infections are limited as no vaccine is available. Prophylaxis with palivizumab is very expensive and requires multiple intramuscular injections over the RSV season. Here we present proof-of-concept data using nebulized palivizumab delivery as a promising new approach for the prevention or treatment of severe RSV infections, documenting both aerosol characteristics and pulmonary deposition patterns in the lungs of lambs. Design Prospective animal study. Setting Biosecurity Control Level 2-designated large animal research facility at the Murdoch Children’s Research Institute, Melbourne, Australia. Subjects Four weaned Border-Leicester/Suffolk lambs at 5 months of age. Interventions Four lambs were administered aerosolized palivizumab conjugated to Tc-99m, under gaseous anesthesia, using either the commercially available AeroNeb Go® or the investigational HYDRA device, placed in-line with the inspiratory limb of a breathing circuit. Lambs were scanned in a single-photon emission computed tomography (SPECT/CT) scanner in the supine position during the administration procedure. Measurements and Main Results Both the HYDRA and AeroNeb Go® produced palivizumab aerosols in the 1–5 µm range with similar median (geometric standard deviation and range) aerosol droplet diameters for the HYDRA device (1.84 ± 1.40 μm, range = 0.54–5.41μm) and the AeroNeb Go® (3.07 ± 1.56 μm, range = 0.86–10 μm). Aerosolized palivizumab was delivered to the lungs at 88.79–94.13% of the total aerosolized amount for all lambs, with a small proportion localized to either the trachea or stomach. No difference between devices were found. Pulmonary deposition ranged from 6.57 to 9.25% of the total dose of palivizumab loaded in the devices, mostly in the central right lung. Conclusions Aerosolized palivizumab deposition patterns were similar in all lambs, suggesting a promising approach in the control of severe RSV lung infections.